Budget optimization for advertisers as contextual advertising market participants - Гальчинський, Леонід Юрійович; Сташкевич, Дмитро Станіславович (Technology audit and production reserves, 2016)
The problem of budget optimizing for advertisers in the market of modern Internet advertising was investigated depending on the choice of strategy of contextual advertising when using the RTB technology and found that the long-term strategy that uses the methodology of statistical arbitrage has good prospects. The importance of this issue is caused by the energetic innovative changes in Internet advertising and by the rapid growth of contextual advertising both in the world and in Ukraine. The conducted testing of the EM-algorithm model in the computer instruction paradigm established a substantial increase in efficiency of an advertiser’s budget use. The conducted numerical modeling using special software has shown that the statistical arbitrage model has some differences, depending on the rate selection parameters, but in all cases it gives better results when statistical arbitrage is not applied. The research results are useful for advertisers because they make it possible to optimize the advertising budget and are important for the Internet advertising market, because they increase its effectiveness in general.